Day hiking. Central Cascades : Stevens Pass, Glacier Peak Wilderness, Lakes Wenatchee & Chelan - Romano, Craig (Mountaineers Books, 2023)
"A guide to the 136 best day hikes in the Washington State region along US 2 from the Sultan Basin to Wenatchee, and from Blewett Pass, Chelan, the Stehekin Valley, and the Entiat River Valley"--